Of hearts and hypertension blazing genetic trails - Christine E. Seidman, lecturer; Richard P. Lifton, lecturer (Howard Hughes Medical Institute, 2006)
Consists of four lectures on the heart, including information on risk factors, advances in diagnostic methods, identifying "disease genes", and genetic factors in hypertension.